Long-term outcomes associated with short-term surgical missions treating complex head and neck disfigurement in Ethiopia: A retrospective cohort study. Issue 5 (May 2020) - Honeyman, C.; Patel, V.; Yonis, E.; Fell, M.; Demissie, Y.; Eshete, M.; Martin, D.; McGurk, M.
Summary: Background: Long-term follow-up after short-term reconstructive missions is challenging, often due to financial constraints, remote geography and lack of post-operative communication with patients. The aim of this study was to conduct long-term follow-up of patients who have undergone surgery for complex facial disfigurement in Ethiopia. Methods: A retrospective cohort study was conducted in Ethiopia over a 2-week period between February and March 2017. All patients who were previously operated on by the charity Project Harar were eligible. Data were collected from semi-structured interviews and clinical examinations. Results: Seventy patients (41 males: 29 females) were included in this study. This equates to a follow-up rate of 20% (70/350) of all patients operated on by the charity since 2008. Mean patient age was 26.8 years (range, 3–61 years). The most common pathologies were noma (24%), ameloblastoma (16%) and trauma (11%). The mean follow-up time after final surgery was 47 months (range, 12–180) with an average of 1.3 (range, 1–6) operations per patient. Long-term complications were reported by 30% of patients, with chronic fistula ( n  = 6) and chronic infection ( n  = 3) the most common. Following surgery, stigma experienced by patients decreased from 92% to 3%. Conclusions: This study demonstrates that complex head and neck reconstruction can be safely undertaken in resource-limited settings with improvements in stigma experienced and quality of life for patients. However, despite a decade of experience and refinements, early and late complications do occur, and this should be factored into pre-mission planning and careful follow-up. New, cost-neutral follow-up protocols are being developed.